Large-scale production: A possible way to the balance between feed grain security and meat security in China - Shuhui Yang; Xuefeng Cui (Journal of Agriculture and Food Research, 2023)
Food security as a national strategy, closely links to China's economic progress, people's livelihoods and social harmony. The balance between feed grain security and meat security remains a key unresolved issue that significantly impacts China's integral food security goal. In this study, we first apply food security index to demonstrate the efficacy of the self-sufficiency rate as an indicator for evaluating the food security situation, and then evaluate meat security and feed grain security with self-sufficiency rate, as well as explore their production challenges and successful long-term development experiences based on related agricultural data. We find that the burgeoning meat consumption has made feed grains a “rigid demand”, among which pork and soybean are critical parts. Pork consumption accounts for over 65% of total meat consumption in 2020, but its self-sufficient rate is waning. Moreover, the self-sufficiency rate of soybean is as low as 0.15, and a great unit yield gap between China and the United States. However, the current production patterns have already reached their attainable potential in production efficiency due to the declining growth rate of unit yield, which also pose challenges for improving production efficiency and domestic supply of soybean. According to the projection by FAO-OECD, the growth rate of unit yield of soybean will remain stagnant from 2020 to 2030. Furthermore, the percentage of medium-scale and large-scale pig farms is remarkably low, accounting for only 0.578% and 0.013%, respectively. Further analysis indicates that large-scale production in soybean and pig industry offers notable advantages in improving production efficiency and reducing feed consumption. Finally, based on factors such as soybean sowing area, regions with high pig slaughter and scale farms, farm size and the pig regional development planning, we propose the integration of soybean-pig in large-scale production in selected possible provinces, which has the potential to improve the production efficiency of soybean and pig, to strike a balance between feed grain security and meat security. This study has practical significance in optimizing the production space of feed grains and livestock products, to improve production capability and ensure China's food security.
Keywords: 630; food security; pig industry; soybean; self-sufficiency; large-scale production